Creative economy and the quintuple helix innovation model: a critical factors study in the context of regional development - Rodrigues-Ferreira, Ariele; Afonso, Herlander; Mello, José André; Amaral, Rebeca (Creativity Studies, 2023)
Creative economy is the area of knowledge that explores the intangible and symbolic aspects and feeds on creative talents, individually and/or collectively organized, in order to produce creative goods and services. This type of economy has its own dynamics, and it disturbs the traditional economic models. This study investigated creative economy comprehensively and aims to analyze the critical factors inherent in the dynamics of creative economy for regional development, considering the helix model of innovation (quintuple helix innovation model), aligned with entrepreneurship and innovation. To this end, the methodology used was systematized exploratory research, treated within three dimensions – the economic-financial, the socio-anthropological, and the techno-innovative. The conclusion of the study was the identification of fifteen critical factors, the direct creative economy relationship with the quintuple helix innovation model in all its helixes, as well as its “Mode 3” of the dynamics of knowledge generation, creation, and dissemination. The study also highlighted the importance of creative economy as one of the “engines” of regional development, in an economic, financial, social, technological, and sustainable way, driven by the government, its networks, and its actors.